Kinetics of Sm3+ extraction by BTMPPA using single drop technique - Md Fazlul Bari; Foo Hing, Heong; Muhammad Idris, Salleh; Bahruddin, Saad (Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 2009)
The rate of Sm(III) extraction from acidic nitratc-acctato medium by bis(2,4,4-trimelhylpentyOphosphoric acid (Cyancx 272, BTMPPA, H2A2) in toluene has been measured by the single drop technique. The rate of mass transfer per unit area is found to be proportional to [Sm3*], [ H2A2](0>, [H*] at the interface. The extraction rate constant, kF. has been determined to be IO"715 m/s. The rare expression can be written as; Fs. - IO'715 [Sm3*][H2A2](o»[rr](1) kmol/m2s Analysis of the rate expression suggests that the formation of [Sm(HA2)]2* at interface from Sm5* and HA^ is the rate-determining step for the extraction of Sm(III).